Health-related quality of life in adults with attention-deficit and hyperactivity disorder - Silva,Maria Aparecida da (2014)
OBJECTIVE Attention-Deficit and Hyperactivity Disorder is a neurodevelopmental condition that causes substantial deficits in several aspects of human function, resulting in a poor quality of life. However, studies using valid reports to objectively document Quality of Life impairment in never-treated adults with Hyperactivity Disorder Self-Report Scale have, to date, been scarce. The aim of this study was to assess Quality of Life in a clinical sample of treatment-naïve adults with Attention-Deficit and Hyperactivity Disorder in comparison to a healthy control group, and to investigate the relationship between Quality of Life and symptom severity ratings. METHOD Symptom severity ratings (assessed using the Attention-Deficit and Hyperactivity Disorder Self-Report Scale) and quality of life measurements using the World Health Organization Quality of Life scale (through WHOQOL-BREF) were obtained from a sample of 46 treatment-naïve adults with Attention-Deficit and Hyperactivity Disorder (mean age=29.3 years) and a group of 28 healthy controls (mean age=28.7 years). RESULTS Quality of Life was significantly worse in the Attention-deficit and Hyperactivity Disorder group compared to the healthy controls. The severity of symptoms of hyperactivity (but not of inattention) was negatively correlated with quality of life. CONCLUSION The use of a generic Quality of Life tool such as the WHOQOL-BREF allows the detection of lower Quality of Life, vs. healthy controls, in adult Attention-Deficit and Hyperactivity Disorder patients, and highlights the relevance of Quality of Life impairment when planning and monitoring treatment strategies for such a population.